2008
DOI: 10.2337/dc08-1034
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Risk of Non-Hodgkin's Lymphoma

Abstract: OBJECTIVE -To examine the epidemiologic association between diabetes and risk of nonHodgkin's lymphoma (NHL).RESEARCH DESIGN AND METHODS -We searched MEDLINE for observational studies on the association between diabetes and NHL in adults using the keywords "diabetes" and "lymphoma." Prospective cohort studies that reported relative risks or standardized incidence ratios and case-control studies that reported odds ratios with 95% CIs were included. A randomeffects model was used to combine results from the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 37 publications
5
83
1
2
Order By: Relevance
“…Our lower estimates relative to this study may be attributed to the use of national population rates as the comparator (rather than a nondiabetic population). SIR estimates for type 2 diabetes obtained in our study are also comparable to previous meta-analyses performed on sitespecific cancer incidence (4,(14)(15)(16)(17)(18)(19)(20). We add to the current literature around type 2 diabetes and cancer incidence more precise risk estimates for some of the less common cancers.…”
Section: Comparison With the Literaturesupporting
confidence: 83%
“…Our lower estimates relative to this study may be attributed to the use of national population rates as the comparator (rather than a nondiabetic population). SIR estimates for type 2 diabetes obtained in our study are also comparable to previous meta-analyses performed on sitespecific cancer incidence (4,(14)(15)(16)(17)(18)(19)(20). We add to the current literature around type 2 diabetes and cancer incidence more precise risk estimates for some of the less common cancers.…”
Section: Comparison With the Literaturesupporting
confidence: 83%
“…Numerous epidemiological studies have identified associations between diabetes and several types of cancer in various populations [9][10][11][12][13][14][15][16][17][18][19] (Table 2). While the literature indicates a strong and consistent increased risk of cancer in people with type 2 diabetes, the strength of association depends on the specific cancer site.…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 99%
“…Risk of endometrial cancer appears to be doubled in women with diabetes [13]. Risks of breast [11], colorectal [12], bladder [15], non-Hodgkin lymphoma (NHL) [16] and kidney [14] cancers are about 20-40% higher in people with type 2 diabetes. Interestingly, prostate cancer is about 10-20% less likely in men with type 2 diabetes, which is thought to be due, in part, to the reduced levels of circulating testosterone in men with diabetes [1,19].…”
Section: Epidemiology Of Diabetes and Cancer Incidencementioning
confidence: 99%
“…Epidemiological studies have shown that diabetes [1][2][3][4][5][6][7] or certain treatments for diabetes may increase the risk [8][9][10] of developing cancer. Diabetes may also affect the treatment of cancer; some types of cancer are treated less aggressively in patients with diabetes than in patients without diabetes [11].…”
Section: Introductionmentioning
confidence: 99%